Designing human centered virtual reality to improve student earthquake preparedness in Bali - Anak Agung Ngurah Adhi Jaya; Luh Putu Cintya Prabandari; Jovita Ridhani; Kadek Dwi Hendratma Gunawan (Journal of Environment and Sustainability Education, 2025)
Indonesia faces one of the highest disaster risks globally, with Bali being a particularly vulnerable region due to its tectonic setting along the Sunda Arc subduction zone. Despite the urgency of disaster education, current approaches in Indonesian schools remain largely conventional, lacking contextual engagement and experiential depth. This study aimed to develop and evaluate a Human-Centered Design (HCD)-based Virtual Reality (VR) simulation to enhance earthquake preparedness among junior high school students in Bali. Employing a mixed-methods approach, the VR media was developed through iterative phases, discover, define, design, and prototype & test, while integrating local context and user needs. Expert validation involving specialists in instructional media and disaster education confirmed the simulation's accuracy, usability, and contextual relevance. Subsequently, a limited implementation was conducted with 101 students in Bali. Students’ understanding was assessed using five open-ended items scored with a four-point rubric, and the data were analyzed using the Wilcoxon Signed-Rank Test and effect size (r). Results showed statistically significant improvement across all indicators (p < .001; r = 0.79–0.93), with clearer mastery of response procedures, improved recognition of safety signals, and more consistent understanding among students. Theoretically, this study expanded the application of HCD in mixed-methods educational research and practically demonstrated the potential of VR as an immersive, user-centered, and contextually relevant disaster learning media.